2023
DOI: 10.1371/journal.pone.0282491
|View full text |Cite
|
Sign up to set email alerts
|

Traditional health practices: A qualitative inquiry among traditional health practitioners in northern Uganda on becoming a healer, perceived causes of illnesses, and diagnostic approaches

Abstract: Background The practice of traditional and complementary medicine is increasing in most low-and middle-income countries especially for chronic communicable and non-communicable diseases. In this study, we aimed to understand how people gain healing power and become traditional health practitioners (THPs), perceived causes of illnesses, and how THPs diagnose illnesses. Methods This was a cross-sectional qualitative interview-based study. We used semi-structured in-depth guides to collect data from THPs identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…Previous researchers documented similar findings, that spiritual calling into healing is an intergenerational familial natural gift (16,23,68). Another researcher found that anointment into healing using ancestral spirits is involuntary, and may manifest through challenges of illness (69).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Previous researchers documented similar findings, that spiritual calling into healing is an intergenerational familial natural gift (16,23,68). Another researcher found that anointment into healing using ancestral spirits is involuntary, and may manifest through challenges of illness (69).…”
Section: Discussionmentioning
confidence: 61%
“…Although the ways spiritual healers obtain their knowledge and skills vary widely (23), and the reliability of ancestral communication and its contextual packaging is highly arguable, the valid sources of exact knowledge stand questionable (78). Some countries, such as China, Korea, India and Vietnam, have established official education/training programs for traditional medicine practitioners at university levels (13,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In addition, the harmful potential of traditional healers lies on the fact that they do not receive authentic academic education in medicine, which is supported by responses of a previous study where traditional healing practitioners were asked about how they diagnose illnesses and majority responded they diagnose illnesses through various approaches including consultations with spirits, observing patterns of occurrences and events, use of bones from animals/birds and other objects to diagnose illnesses, and performing diagnostic rituals. 23 The strength of this study is that it is the first study to tackle traditional medicine in the region of North Kordofan, including participants of both genders, various age groups, and cultural and religious beliefs, which we believe that the findings reported would be of benefit towards better healthcare distribution and would be the sparkle to focus the light on the issue of traditional medicine in Sudan as a whole.…”
Section: Discussionmentioning
confidence: 94%